Profile of a Liver Transplant Follow-Up Clinic in a Nontransplant Canadian Urban Centre. (1st April 1997) - Bazylewski, R; Rosser, BG; Cohen, A; Kaita, KDE; Minuk, GY
Abstract : Care of the growing number of liver transplant recipients will increasingly fall on the referring centres. Thus, there is a need to define more clearly the demographic, clinical and laboratory profiles of liver transplant recipients, particularly in the setting of a centre where a liver transplantation program does not exist. The present study documented these features in 37 patients attending an adult ambulatory care clinic in an urban, nonliver transplant centre. Mean ± SD age of the study population was 44±11.9 years. Twenty-one patients (57%) were male. Annual enrolment in the clinic increased from three patients at the completion of the clinic's first year (1988) to 16 patients in the final year of the study (1993). Time between the transplantation procedure and the patient's return to the referring centre decreased from a mean of 12 weeks in 1988 to four weeks in 1993. During those seven years no patient required an unscheduled return to the transplant centre for surgical complications or problems associated with immunosuppressive therapy. In conclusion, these data provide a profile of liver transplant patients attending a nonliver transplant centre for follow-up and support the concept that nontransplant centres are capable of providing safe and, in terms of travel, less expensive care for liver transplant recipients.